Influence of TiO2 electronic structure and strong metal–support interaction on plasmonic Au photocatalytic oxidations. Issue 9 (16th December 2015) - Naldoni, Alberto; Riboni, Francesca; Marelli, Marcello; Bossola, Filippo; Ulisse, Giacomo; Di Carlo, Aldo; Píš, Igor; Nappini, Silvia; Malvestuto, Marco; Dozzi, Maria Vittoria; Psaro, Rinaldo; Selli, Elena; et al.
Abstract : Photocatalytic oxidations promoted by hot electron transfer and PRET strongly depend on Au loading and SMSI. Abstract : Aiming at understanding how plasmonic reactions depend on important parameters such as metal loading and strong metal–support interaction (SMSI), we report the plasmonic photodegradation of formic acid (FA) under green LED irradiation employing three TiO2 supports (stoichiometric TiO2, N-doped TiO2, black TiO2 ) modified with Au nanoparticles (NPs) 3–6 nm in size. The rate of FA photooxidation follows different trends depending on Au loading for stoichiometric and doped Au/TiO2 materials. In the first case, the only contribution of hot electron transfer produces a volcano-shaped curve of photoreaction rates with increasing Au loading. When TiO2 contains intra-bandgap states the photoactivity increases linearly with the amount of Au NPs due to the concomitant enhancement produced by hot electron transfer and plasmon resonant energy transfer (PRET). The role of PRET is supported by finite element method simulations, which show that the increase in both Au NP inter-distance and SMSI enhances the probability of charge carrier generation at the Au/TiO2 interface.